Early Esophageal Squamous Cell Carcinoma on Varix Treated With Endoscopic Submucosal Dissection After Variceal Banding - Shiratori, Yasutoshi (ACG Case Rep J, 2019)
Endoscopic submucosal dissection (ESD) is known as a representative therapy for the early esophageal carcinoma, but an underlying varix is an obstacle to perform ESD. Patients with alcoholic cirrhosis may develop esophageal varix and esophageal squamous cell carcinoma at the same time. We report a case of early esophageal squamous cell carcinoma just above the esophageal varix. We performed the combination therapy of variceal banding and ESD. The number of reports about the combination therapy and optimal time to perform variceal banding before ESD is not sufficient.